Tourist Complex of South of Russia in the Current Conditions: The Krasnodar Region and the Republic of Crimea - Volkova, Tatiana Aleksandrovna; Minenkova, Vera Vladimirovna; Mishchenko, Alexandr Aleksandrovich; Razumov, Viktor Vladimirovich; Belikov, Mikhail Yuryevich (International Review of Management and Marketing, 2016)
In whole, the tourist recreational complex of the Krasnodar Region is similar to the tourist recreational complex of the Crimea Republic: in density of population, in enterprise proportions of agriculture and tourism, in climate and peculiarities of territorial specialization. The purpose of investigation was to determine possible development ways of tourist recreational complex of Russian South in new geo-economical and geopolitical conditions. A comparative study of these two tourist regions, existed in almost equal development conditions for many decades, was carried out as per such categories, as the prices, the service and the climate. The Krasnodar Region, undoubtedly, wins in the bulk of tourist visits, in quantity of accommodation service, quality of infrastructure and quantity of working resorts, level of medical assistance. The Crimea Republic is more attractive by lower prices, wider spectrum and efficiency of natural resources, used for recreation. The Crimea Republic and the Krasnodar Region are unique from the viewpoint of their health-improving potential. The changes of geopolitical and geo-economical character introduce definite corrections to the development directions of tourist recreational complexes of the Krasnodar Region and the Crimea Republic. Both regions are characterized by definite positive features, although there are some disadvantages, which are to be eliminated. From our point of view, both regions are able to develop the tourist recreational complex maximally in case of cooperation. Keywords: tourism, tourist recreational complex, the Krasnodar Region, the Crimea Republic JEL Classifications: L83, P25